Assessing Profitability, Marketing Activities and Problems in Modern Rice Production in Two Northern Districts of Bangladesh (The Agriculturists, 2019)
This study estimated the cost and revenue of BRRI dhan 28 productions in two districts namely, Bogura and Gaibandha in Bangladesh. The paper also identifies farmers marketing activity and their production problems. Primary data were collected from 60 farm household’s survey using pretested semi-structured questionnaire during November to December, 2017. Farm level production and profitability were analysed by using net farm incomes and Benefit Cost Ratio (BCR) taking into account the variable cost and total cost. Applying descriptive statistics, the analysis showed that total cost of paddy production was higher in Bogura (BDT 44,555.3/acre) compared that of Gaibandha (BDT 42,199.5/acre) while net farm income was higher in Gaibandha (BDT 32992.2/acre) than Bogura (BDT 32475.9/acre). The analysis further showed that paddy production was profitable in both districts. BCR on the basis of variable cost and total cost indicated that return from paddy production was higher than cost which also ensures farmers profit in paddy production in both the districts. According to farmers’ opinion, disease infestation was the major production problem in Bogura district while both disease attack and natural calamities were the major production problems in Gaibandha district. Farmers’ suggested to reduce the cost of pesticides and they need marketing facilities to sell their product. They also suggested to establish cold storage facilities which create the opportunity to get fair price for their product.The Agriculturists 2019; 17(1-2) 31-40